Synthesis, characterization and in silico biological activity of some 2-(N,N-dimethyl guanidinyl)-4,6-diaryl pyrimidines - Rajasekhar Komarla Kumarachari; Sivakumar Peta; Abdrrahman Shemsu Surur; Yenus Tadesse Mekonnen (Wolters Kluwer Medknow Publications, 2016)
Introduction: As pyrimidine is a basic nucleus in DNA and RNA, it has been found to be associated with diverse biological activities.Pyrimidine derivatives were reported to possess anticonvulsant, antimicrobial, anti-inflammatory, antitumor, and antihistaminic. Recently, our team reported the anti-inflammatory and antimicrobial evaluation of some pyrimidines. Objective: To synthesize, predict and evaluate biological activity of some 2-(N,N-dimethyl guanidinyl)-4,6-diaryl pyrimidines. Experimental: seven new pyrimidines were synthesized by following the standard procedures using substituted aromatic aldehydes, methyl ketones and metformin. After the biological activity was predicted using PASS, Molinspiration and Osiris property explorer, their anthelmintic activity was evaluated using Pheretima posthuma. The structural assignment of the title compounds (P1-7) has been made on the basis of elemental analysis, infrared, 1H-nuclear magnetic resonance and Mass spectral studies. Results: All the synthesized compounds were found to obey Lipinski's rule. All the synthesized compounds scored good bioactivity values as GPCR ligands and kinase inhibitors. Among the test compounds, P5 was found to be more potent anthelmintic inducing paralysis in 36-48 minutes and death in 40-51 minutes. Conclusion and Recommendation: The synthesized compound (P5) possessing methoxy group at position-4 of the benzene ring located at position-4 of pyrimidine exhibited good anthelmintic activity. The study revealed the necessity of synthesizing many more compounds with other substituents at position-4 of the benzene ring located at position-4 of pyrimidine.